2010
DOI: 10.1007/s10488-010-0294-z
|View full text |Cite
|
Sign up to set email alerts
|

Stigma in Child and Adolescent Mental Health Services Research: Understanding Professional and Institutional Stigmatization of Youth with Mental Health Problems and their Families

Abstract: To understand the low utilization rates of child and adolescent mental health services, it is necessary to recognize the kinds of professional and institutional stigma that may produce barriers to care. We address the large literature on the stigmatization of mental illness, linkages between such literature and children's mental health services use, and the kinds of professional and institutional attitudes and practices that communicate shame and low expectations to youth and their families. It will take recog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
102
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 130 publications
(107 citation statements)
references
References 56 publications
(57 reference statements)
0
102
0
1
Order By: Relevance
“…Taking aim at clinical practice, Alegria et al (2010) argue that traditional clinical approaches to child mental health too often fail youth from diverse backgrounds by ignoring culture and context. Heflinger and Hinshaw (2010) exhort providers to change their own attitudes and behaviors to reduce the stigma that thwarts effective care. In sum, these articles call for major overhaul of the mental health systems that currently serve youth in order to remedy the pervasive inadequacies in quality, quantity, reach, and coordination of care.…”
mentioning
confidence: 99%
“…Taking aim at clinical practice, Alegria et al (2010) argue that traditional clinical approaches to child mental health too often fail youth from diverse backgrounds by ignoring culture and context. Heflinger and Hinshaw (2010) exhort providers to change their own attitudes and behaviors to reduce the stigma that thwarts effective care. In sum, these articles call for major overhaul of the mental health systems that currently serve youth in order to remedy the pervasive inadequacies in quality, quantity, reach, and coordination of care.…”
mentioning
confidence: 99%
“…Further, Newton et al [10] have reported on the effect of sociodemographic factors on the number of visits to emergency services by mental health patients, primarily focusing on sociodemographic status and risk of an individual's return to the emergency department. Hefflinger and Hinshaw [7] have reported that stigma exists at professional and institutional levels and is the reason for low health care utilization among children and adolescents with mental disorders seeking mental health services. The present study extends our understanding by examining the consequences for youth on being labelled with a psychiatric disorder when seeking health services for physical disorders.…”
Section: Resultsmentioning
confidence: 99%
“…While the reasons for such findings remain under debate, Heflinger and Hinshaw [7] present one explanation based on professional and institutional stigma that exists for child and adolescent patients seeking help for mental disorders. Evidently, system-based stigma and societal stigma are a great barrier to the treatment of psychiatric disorders in children.…”
mentioning
confidence: 99%
“…14,15). Institutional stigma can be as real and as impactful as other forms of stigma (Heflinger & Hinshaw, 2010) and the data from this present research suggests that organisational context can have an important influence in working in such an environment.…”
Section: The Importance Of Reflexivity In the Organisationmentioning
confidence: 60%
“…Heflinger and Hinshaw (2010) contend that not recognising 'the multiple and intersecting aspects' of the young person's life -such as family -and exclusively focusing on the mental health disorder, is one expression of institutional stigma (pp. 62,63).…”
Section: The Importance Of Reflexivity In the Organisationmentioning
confidence: 99%